1999
DOI: 10.1105/tpc.11.12.2291
|View full text |Cite
|
Sign up to set email alerts
|

RNA–DNA Interactions and DNA Methylation in Post-Transcriptional Gene Silencing

Abstract: Post-transcriptional gene silencing (PTGS) is a homology-dependent process that reduces cytoplasmic RNA levels. In several experimental systems, there is also an association of PTGS with methylation of DNA. To investigate this association, we used plants carrying a transgene encoding the green fluorescent protein (GFP). Gene silencing was induced using potato virus X RNA vectors carrying parts of the coding sequence or the promoter of the GFP transgene. In each instance, homology-based, RNA-directed methylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
226
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 405 publications
(233 citation statements)
references
References 45 publications
(56 reference statements)
7
226
0
Order By: Relevance
“…Such negative co-regulation by a transposon-derived read-through transcript could be achieved by the formation of aberrant genic RNAs that are fueled into a posttranscriptional gene silencing (PTGS) pathway that erases homologous mRNAs within the cluster. Such a pathway would be in favor with regard to the observed rapid regain of transcriptional activity under recovery conditions when read-through transcription ceases, since PTGS of endogenous genes (in contrast to transgenes) is not necessarily associated with the acquisition of epigenetic marks on the DNA (Stam et al, 1998; Jones et al, 1999). In summary, we show that a successful heat response in Arabidopsis depends on the integrity of epigenetic pathways and provide evidence that heat-dependent gene expression is influenced by closely located transposon sequences.…”
Section: Discussionmentioning
confidence: 99%
“…Such negative co-regulation by a transposon-derived read-through transcript could be achieved by the formation of aberrant genic RNAs that are fueled into a posttranscriptional gene silencing (PTGS) pathway that erases homologous mRNAs within the cluster. Such a pathway would be in favor with regard to the observed rapid regain of transcriptional activity under recovery conditions when read-through transcription ceases, since PTGS of endogenous genes (in contrast to transgenes) is not necessarily associated with the acquisition of epigenetic marks on the DNA (Stam et al, 1998; Jones et al, 1999). In summary, we show that a successful heat response in Arabidopsis depends on the integrity of epigenetic pathways and provide evidence that heat-dependent gene expression is influenced by closely located transposon sequences.…”
Section: Discussionmentioning
confidence: 99%
“…PCR products of PSR1 , PSR1M , Δ PSR1 (with point mutations generating a stop codon three amino acids into the PSR1 ORF), PSR2 and Δ PSR2 (with point mutations generating a stop codon eight amino acids into the PSR2 ORF) were ligated into the pGR106 vector 37 , which carries the full PVX genome. Recombinant plasmids were transformed into A. tumefaciens strain GV3101, and the resulting strains were then used to infiltrate 3-week-old wild-type N. benthamiana plants.…”
Section: Methodsmentioning
confidence: 99%
“…RNA gel blot analysis of the genes targeted in our study exhibited strongly reduced target transcript levels in RNAi transgenic cells, suggesting that endogenous transcript accumulation of the targeted gene is the only target-specific determinant of RNAi effectiveness in the four species tested. However, it is reported that factors may affect RNAi effectiveness in a gene-specific manner including sequence composition, spatial and temporal gene expression patterns, and the normal RNA turnover rate of the targeted gene (57., 58., 59.). …”
Section: Discussionmentioning
confidence: 99%